Galli-Galli Disease: A Rare Acantholytic Variant of Dowling-Degos Disease - J. Gomes; J. Labareda; I. Viana (Case Reports in Medicine)
Galli-Galli disease is a rare acantholytic variant of Dowling-Degos disease, with few cases reported in the literature. We describe a case of Galli-Galli disease and review the literature.